Large cyst of the vaginal wall in pregnancy. Issue 9 (8th August 2019) - Papapanagiotou, Ioannis K.; Chatzipapas, Ioannis; Koutroumanis, Pelopidas; Marinopoulos, Spyridon; Thomakos, Nikolaos; Brozou, Maria; Ntzeros, Konstantinos; Petrakis, Evangelos; Diakosavvas, Michalis; Fasoulakis, Zacharias; Morphopoulos, George; Loutradis, Dimitrios
Abstract: Large vaginal cysts during pregnancy are rare and can mislead Obstetricians to a false diagnosis, that of "Protruding membranes". Aspiration of the cyst can be easily performed, resulting in the collapsing of the cyst and an uneventful vaginal delivery can be conducted. Abstract : Large vaginal cysts during pregnancy are rare and can mislead Obstetricians to a false diagnosis, that of "Protruding membranes". Aspiration of the cyst can be easily performed, resulting in the collapsing of the cyst and an uneventful vaginal delivery can be conducted.